SISTEM VERIFIKASI BPHTB SECARA ONLINE TERHADAP TRANSAKSI JUAL BELI TANAH DAN/ATAU BANGUNAN APABILA TERDAPAT KURANG BAYAR PAJAK - Iswara, Septia Jati; Andraini, Fitika (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
The problems in this research are (1). How to verify online Acquisition Duty of Right on Land and Building (BPHTB) for sale and purchase transactions by Land Deed Officials (PPAT) if there is an underpayment of taxes, (2). What factors causing underpayment of Land and Acquisition Duty of Right on Land and Building (BPHTB) tax after online verification, and (3). How to settle the underpayment of Acquisition Duty of Right on Land and Building (BPHTB) tax after online verification. The method in this study is to use normative juridical research methods, legal research on literature which is carried out by examining library materials or secondary data. The research that has been conducted has found that the implementation of e-BPHTB tax payments and the implementation of BPHTB verification by PPAT Nurwulandari, SH. has been carried out according to the procedure and is in accordance with the regulations. Factors that can lead to underpayment of BPHTB taxes are when there is a discrepancy between the condition of the tax object and the market value of the tax object during the BPHTB tax verification process through field research. Settlement of BPHTB tax underpayment is carried out by paying the nominal deficiency by showing the underpaid SSPD-BPHTB. It is hoped that in the implementation of BPHTB tax verification, there will be more teams at Bapenda Semarang so that the document correction process for the issuance of verified SSPD-BPHTB will be faster.